Peppermint protocol: first results for gas chromatography-ion mobility spectrometry. (1st July 2022) - Ruszkiewicz, Dorota M; Myers, Renelle; Henderson, Ben; Yusof, Hazim; Meister, Austin; Moreno, Sergi; Eddleston, Michael; Darnley, Kareen; Nailon, William H; McLaren, Duncan; Lao, Yvonne E; Hovda, Knut Erik; et al.
Abstract: The Peppermint Initiative seeks to inform the standardisation of breath analysis methods. Five Peppermint Experiments with gas chromatography-ion mobility spectrometry (GC-IMS), operating in the positive mode with a tritium 3 H 5.68 keV, 370 MBq ionisation source, were undertaken to provide benchmark Peppermint Washout data for this technique, to support its use in breath-testing, analysis, and research. Headspace analysis of a peppermint-oil capsule by GC-IMS with on-column injection (0.5 cm 3 ) identified 12 IMS responsive compounds, of which the four most abundant were: eucalyptol; β -pinene; α -pinene; and limonene. Elevated concentrations of these four compounds were identified in exhaled-breath following ingestion of a peppermint-oil capsule. An unidentified compound attributed as a volatile catabolite of peppermint-oil was also observed. The most intense exhaled peppermint-oil component was eucalyptol, which was selected as a peppermint marker for benchmarking GC-IMS. Twenty-five washout experiments monitored levels of exhaled eucalyptol, by GC-IMS with on-column injection (0.5 cm 3 ), at t = 0 min, and then at t + 60, t + 90, t + 165, t + 285 and t + 360 min from ingestion of a peppermint capsule resulting in 148 peppermint breath analyses. Additionally, the Peppermint Washout data was used to evaluate clinical deployments with a further five washout tests run in clinical settings generating an additional 35 breath samples. Regression analysis yielded an average extrapolated time taken for exhaled eucalyptol levels to return to baseline values to be 429 ± 62 min (±95% confidence-interval). The benchmark value was assigned to the lower 95% confidence-interval, 367 min. Further evaluation of the data indicated that the maximum number of volatile organic compounds discernible from a 0.5 cm 3 breath sample was 69, while the use of an in-line biofilter appeared to reduce this to 34.